Virtual laboratories for physical anthropology - Kappelman, John W.; Wadsworth Publishing Company (Belmont, Calif. Wadsworth, 2000)
An instructional module that combines a wide range of digital images, three-dimensional animations, video, sound, glossaries, references, laboratory exercises, and self quizzes. Designed to be used as a stand-alone medium or can be used to supplement hands-on teaching.
Title from disc label.
Keywords: Physical anthropology -- Laboratory manuals; Primates -- Evolution; Primates -- Classification; Human evolution